YOUNG ATHLETES AND THEIR HEALTH AWARENESS AS A VALUE - Graczyk, M.; Skalski, D. W.; Czarnecki, D.; Kowalski, D.; Zarichniuk, I.; Starikov, V. (Rehabilitation and Recreation, 2022)
The primary responsibility for spreading and promoting health at school, but also beyond school boundaries, rests with physical education teachers. Their main duties include conducting effective classes and coordinating all activities related to physical education, health, sport and tourism at school. They should explain the importance of this movement for health and human existence. The aim of the study was to investigate the position of the concept of health in the consciousness of more and less athletic youth and what students aged 16 to 18, i. e. high school students, understand by the concept of health. Then we wanted to compare: whose school students show a greater intensity of health-promoting behaviors, mainly the intensification of four categories of health-related behaviors, which are proper eating habits, preventive behavior, health practices and positive mental attitude. Next, we would like to find out what evaluation of the value of health is assigned by students of these schools in the context of other personal rights and values important for a human being. Comparing the results of the respondents of both sexes, it turned out that the value of health is more in the consciousness of boys. Then, comparing the results of the girls, it turned out that girls from the agricultural school were definitely better off. Summing up, we would like to state that a large part of high school and agricultural school students are aware of the factors influencing their health condition and, most importantly, take actions to improve their health. Therefore, these factors could be used in health education, in which the personal needs of young people should be highlighted.